Penguatan Literasi Membaca di Sekolah Dasar melalui Model Project-Based Learning (PBL) sesuai Kurikulum Merdeka - Tehsa Aprilia; Suci Afriyanti; Nurtri Wela; Azilla Fauza; Sry Apfani (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The low level of reading literacy in primary schools remains a serious issue in Indonesia’s education system. This article aims to conceptually examine the role of the Project-Based Learning (PBL) model in strengthening reading literacy, particularly within the implementation framework of the Merdeka Curriculum. This study employed a literature review method by analyzing various relevant academic sources. The findings suggest that PBL has significant potential to improve students’ reading literacy skills, as it emphasizes active, reflective, collaborative, and contextual learning. PBL encourages students to read, comprehend, evaluate, and communicate information in multiple formats, thereby directly enhancing critical, informational, and expressive literacy aspects. Furthermore, PBL is highly compatible with the principles of the Merdeka Curriculum, such as differentiated learning and the Projek Penguatan Profil Pelajar Pancasila (P5). With proper design and institutional support, PBL can serve as a transformative learning strategy to strengthen reading literacy at the primary school level.